An Integrated Framework for Commodity Supply Chain in Higher Educational Institutes (HEIs) - Sharath Kumar, K. M. (Prabandhan: Indian Journal of Management, 2011)
Collaborative commerce ensures adding value at every intermediate stage in the supply chain and now-a-days, it is recognized as a powerful source of competitive advantage. This concept of adding value can be applied to the educational scenario with higher educational institution’s (HEIs) procuring multi-commodities. Rationale for the study has been to eliminate legacy procurement system and implement industry models in HEIs based on value and importance of multiple commodities. An attempt has been made to model commodity supply chain, which will add value to HEIs.. The approach to the study has been carried out using product categorization matrix, which helped to segregate the commodities as general, bulk purchase, critical and strategic commodities. Mathematical modeling of these items has been formulated using the economies of scale for general and bulk purchase category, uncertainty for critical category and product availability for strategic category. Frameworks for different category commodities have been constructed using spreadsheets. Lastly, assimilation of the proposed model has been validated by using MSRSAS data. Results showed significant savings in supply chain cost. Critical items have been evaluated in terms of cycle service level and fill rate. Finally, based on the demand pattern, suitable inventory levels for multi-commodities have been suggested.